Risk Management Policy Implementation in Local Government: An Analysis Based on George C. Edward III Theory - Nur Fajrina Uswatun Hasanah; Muhamad Yopan (Universitas Muhammadiyah Gorontalo, 2026)
Risk management has become a fundamental component of contemporary public governance, particularly in promoting accountability, organizational performance, and sustainable public service delivery. Despite the establishment of regulatory frameworks, the implementation of risk management policies in Indonesian local governments remains inconsistent due to various institutional and organizational constraints. This study aims to analyze the determinants influencing risk management policy implementation by employing George C. Edward III's policy implementation framework, which emphasizes four interrelated dimensions: communication, resources, implementers' disposition, and bureaucratic structure. The study adopts a Systematic Literature Review (SLR) approach following the PRISMA 2020 guidelines. Relevant literature published between 2020 and 2025 was identified through Scopus and Google Scholar databases, resulting in 17 eligible studies for thematic synthesis. The findings reveal that all four dimensions significantly influence the effectiveness of risk management implementation. Resource capacity, particularly the availability of competent human resources, technical expertise, budget allocation, and information systems, emerged as the most critical determinant. In addition, ineffective policy communication, limited commitment among implementing actors, and fragmented bureaucratic structures hinder the institutionalization of risk management practices. The analysis further demonstrates that these dimensions interact dynamically, indicating that isolated policy interventions are insufficient to achieve sustainable implementation. Therefore, strengthening communication strategies, enhancing organizational capacity, fostering leadership commitment, and improving bureaucratic coordination are essential for advancing risk management implementation in local governments. This study contributes an integrated analytical perspective that enriches the literature on public policy implementation while providing practical recommendations for strengthening governance and public sector risk management in Indonesia.